2021
DOI: 10.3390/ijms22126294
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exogenous Auxin Treatment on Cell Wall Polymers of Strawberry Fruit

Abstract: The role of auxin in the fruit-ripening process during the early developmental stages of commercial strawberry fruits (Fragaria x ananassa) has been previously described, with auxin production occurring in achenes and moving to the receptacle. Additionally, fruit softening is a consequence of the depolymerization and solubilization of cell wall components produced by the action of a group of proteins and enzymes. The aim of this study was to compare the effect of exogenous auxin treatment on the physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 72 publications
(158 reference statements)
0
13
0
Order By: Relevance
“…The second stage or disassembly of the cell wall stage corresponds to the temperature range of 180 to 350 °C ( Figure 1 ), where it is possible to observe the greatest differences between the samples. Region three with temperatures above 380 °C corresponds to the residue’s own cell and is not related to the cell wall [ 13 ]. The result shows that the aerial tissue has a high thermal stability ( Figure 1 ); therefore, it is less stable and more prone to enzymatic degradation [ 32 ], and this difference can be related to its higher content in acetyl and hydroxyl groups [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second stage or disassembly of the cell wall stage corresponds to the temperature range of 180 to 350 °C ( Figure 1 ), where it is possible to observe the greatest differences between the samples. Region three with temperatures above 380 °C corresponds to the residue’s own cell and is not related to the cell wall [ 13 ]. The result shows that the aerial tissue has a high thermal stability ( Figure 1 ); therefore, it is less stable and more prone to enzymatic degradation [ 32 ], and this difference can be related to its higher content in acetyl and hydroxyl groups [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the percentage of mass loss, in the first region of thermal degradation, no differences were observed between the samples, with percentage loss values to the aerial tissue and root dries of 3.07% and 2.75%, respectively ( Table 1 ). For the second region of thermal degradation, the average difference was 2.13% between the two samples ( Table 1 ), which can be explained by the differences in the polymeric composition of the two samples (mainly cellulose, hemicellulose, and other) [ 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies on hormonal regulation of NC fruit ripening were mainly based on pharmacological experiments. Unlike the regulation of CL fruit ripening with ethylene as a major regulator, nearly all hormones have been reported to play an important role in NC fruit ripening ( Given et al, 1988 ; Creelman and Mullet, 1997 ; Symons et al, 2006 ; Concha et al, 2013 ; Preuß et al, 2014 ; Jia et al, 2016 ; Coelho et al, 2019 ; Gu et al, 2019 ; Dong et al, 2020 ; Vincent et al, 2020 ; Castro et al, 2021 ; Clayton-Cuch et al, 2021 ; Figueroa et al, 2021 ; Kou et al, 2021 ; Li et al, 2022 ). To date, it is hard to conclude which hormone may be the key regulator controlling NC fruit ripening.…”
Section: Hormonal Regulation Of Nc Fruit Ripeningmentioning
confidence: 99%
“…While abscisic acid (ABA) has been proposed to play an important role in NC fruit ripening ( Kumar et al, 2014 ; Forlani et al, 2019 ; Fenn and Giovannoni, 2021 ; Kou et al, 2021 ; Li et al, 2021 ), there are evidence that many other hormones may also play crucial roles in NC fruit ripening. For example, auxin ( Given et al, 1988 ; Gu et al, 2019 ; Vincent et al, 2020 ; Castro et al, 2021 ; Clayton-Cuch et al, 2021 ; Li et al, 2022 ), giberelin ( Kou et al, 2021 ), jasmonic acid ( Creelman and Mullet, 1997 ; Concha et al, 2013 ; Preuß et al, 2014 ; Jia et al, 2016 ; Coelho et al, 2019 ; Li et al, 2022 ), Brassinosteroids ( Symons et al, 2006 ), and even ethylene ( Dong et al, 2020 ; Figueroa et al, 2021 ), all these hormones have been reported to be involved in the regulation of strawberry fruit ripening. Importantly, as early as 1980s, a classic study by Given et al (1988) demonstrated that removal of achenes from receptacle induced fruit ripening, and it was concluded that a decrease in the level of auxin (IAA) in receptacle might act as a signal regulating strawberry fruit ripening.…”
Section: Introductionmentioning
confidence: 99%